Managing supplier satisfaction: Social capital and resource dependence frameworks. Issue 2 (May 2015) - Schiele, Holger; Ellis, Scott C.; Eßig, Michael; Henke, John W.; Kull, Thomas J.
Abstract: Recently, supplier satisfaction has gained more attention both in practice and in academic research. However, the knowledge accumulation process is still in an embryonic and explorative phase. Likewise, supplier satisfaction measuring in practice may still benefit from an impetus from academia to be more widely used. This paper aims at considerably expanding understanding of supplier satisfaction by proposing to apply a social capital and a resource dependence theory perspective. We expect an abundance of social capital in a relationship to relate positively to supplier satisfaction, whilst power disequilibrium and dependence from the buyer are expected to negatively relate to supplier satisfaction. It is worth highlighting that, according to research rooted in Hofstede's cultural dimensions model, the perception and acceptance of power differences resulting from a situation of dependency is highly culture specific. We therefore further hypothesise that supplier satisfaction will be moderated by cultural differences and ask researchers to take the cultural dimension into account. Chinese abstract: 近来，供应商的满意度得到了更多的关注，无论是在实践中还是在学术研究领域。但是，知识的积累过程还处于萌芽和探索阶段。同样，将学术推动力更广泛地付诸于实践也有益于衡量供应商的满意度。本文提议采用社会资本和资源依赖理论的角度，旨在极大地提高对供应商满意度的理解。我们预计巨大的社会资本会出现在供应商和客户关系中，而这将会与供应商的满意度有积极的关联，但是权力的不平衡和来自购买方的依赖性预计将会消极地影响供应商的满意度。值得强调的是，根据以Hofstede的文化维度模型为基础的研究表明，对于因依赖而产生的权力差异的感知和接受有着极高的文化特定性。因此，我们做出了进一步假设，即供应商的满意度将会通过文化的差异来调节，并要求研究人员将文化的维度纳入考虑。